Charles Scott correspondence - Scott, Charles, 1739-1813.
ALS written by Scott to U.S. secretary of war Henry Dearborn concerning the acquisition of land near Newport, Ky., for an arsenal.
Governor of Kentucky and army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Dearborn, Henry, -- 1751-1829 -- Correspondence; Arsenals -- Kentucky; Land tenure -- Kentucky; Newport (Ky.) -- History; Army officers; Governors -- Kentucky